ARCHITECTING A WEB-BASED ONLINE PSYCHOLOGICAL TEST PROCTORING REPORT APPLICATION - Fahrurroji, Fahri Muhammad; Salim, Agus (Simtek : jurnal sistem informasi dan teknik komputer, 2025)
The proctoring report process at PT Hara Anargya Indonesia is still conducted manually via WhatsApp, causing inefficiencies in scheduling, reporting, and coordination. This study aims to design and develop a web-based application to improve the efficiency and accuracy of online psychological test proctoring. Using the Rapid Application Development (RAD) method, the system was built with NestJS, Vue.js 3, and MySQL for modularity and maintainability. Data collection involved field observations, internship experience, and literature reviews. In this system, proctors play a key role by managing their schedules, accepting or declining assignments, as well as createing and submitting supervision reports digitally. The Assessment Division schedules tasks and monitors progress, while the Research Division reviews and validates submitted reports. Black box testing confirmed the system's core features run effectively. The results show the application's readiness for real-world use and its potential to streamline the reporting process while improving data consistency and traceability.